Factor Immobility and Regional Impacts of Trade Liberalization Evidenceon Poverty From India - Topalova, Petia (IMF Working Papers; Working Paper ;, 2010)
This paper uses the 1991 Indian trade liberalization to measure the impact of trade liberalization on poverty, and to examine the mechanisms underpinning this impact. Variation in sectoral composition across districts and liberalization intensity across production sectors allows a difference-in-difference approach. Rural districts, in which production sectors more exposed to liberalization were concentrated, experienced slower decline in poverty and lower consumption growth. The impact of liberalization was most pronounced among the least geographically mobile, at the bottom of the income distribution, and in Indian states where inflexible labor laws impeded factor reallocation across sectors.